Job stress in young adults is associated with a range of poorer health behaviors in the childhood determinants of adult health (CDAH) study - Wang, S; Sanderson, K; Dwyer, T; Venn, A; Gall, S (Lippincott, Williams & Wilkins, 2018)
Objective: To examine job stress and health behaviors, including their co-occurrence, in Australians aged 31 to 41 year assessed in 2009 to 2011. Methods: Cross-sectional analyses using multivariable regression models of the association between the Effort Reward Imbalance (ERI) scale and health behaviors (smoking, alcohol consumption, diet, physical activity, and body mass index [BMI]) both individually and co-occurring (0 to 3 vs 4 to 5 behaviors) were undertaken. Covariates included sociodemographics, personality, and life events. Results: Greater ERI was associated with a significantly lower prevalence of having co-occurring healthy behaviors and poorer diets in both sexes. Higher ERI was also associated greater physical inactivity and sedentary behavior in men and smoking, high alcohol consumption, and more pedometer-measured physical activity in women. Conclusion: Job stress at work was associated with a range of unhealthy behaviors, which may explain the higher chronic disease associated with job stress.